In silico drug discovery for potential epidermal growth factor receptor agonists - Han, Hao (Nanyang Technological University, 2024)
This study presents a novel approach in the field of in silico drug discovery, targeting the Epidermal Growth Factor Receptor (EGFR) to identify potential agonists. Utilizing structure-based virtual screening, the research identifies small molecules capable of binding to EGFR's extracellular domain. The methodology includes molecular docking and dynamic simulations to predict binding conformations and analyze ligand-protein interaction stability. This research contributes to the development of therapeutic agents in cancer treatment by focusing on stabilizing the transforming growth factor alpha (TGF-α) /EGFR complex, highlighting promising compounds for future in vitro and in vivo testing.